Comprehensive Principle of HPLC Fingerprint in the Construction and Evaluation of Chinese Herbal Medicine - Gu, PhD, Jian; Tan, PhD, Rui; Li, MD, Shengmao (North American Journal of Medicine and Science, 2010)
The establishment of a Chinese herbal medicines quality control system is at the core of the modernization development of Chinese medicine. High Performance Liquid Chromatography (HPLC) fingerprint technology is applied to quality control of Chinese herbal medicines from the perspective of systems biology and depends on the classical theory of Chinese medicine system together with information processing technology. In the view of the characteristics of Chinese medicine and the development and application of the top-notch technology in recent years, we tried to integrate information and establish a standard evaluation system of Chinese medicine by using standard chromatographic fingerprints, with a view to improve Chinese medicine quality control and modernization of Chinese medicine development.